2016
DOI: 10.1007/978-3-319-45153-4_6
|View full text |Cite
|
Sign up to set email alerts
|

“Keep Your Eyes on ’em all!”: A Mobile Eye-Tracking Analysis of Teachers’ Sensitivity to Students

Abstract: International audienceThis study aims at investigating which cues teachers detect and process from their students during instruction. This information capturing process depends on teachers' sensitivity, or awareness, to students' needs, which has been recognized as crucial for classroom management. We recorded the gaze behaviors of two pre-service teachers and two experienced teachers during a whole math lesson in primary classrooms. Thanks to a simple Learning Analyt-ics interface, the data analysis reports, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 15 publications
1
38
1
2
Order By: Relevance
“…Videos have been effective in comparing and measuring ways that experienced and novice teachers attend to particular moments in recorded classrooms (Dessus, Cosnefroy, & Luengo, 2016; Cortina, Miller, McKenzie, & Epstein, 2015; van den Bogert, Bruggen, Kostons, & Jochems, 2014). For example, Dessus et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Videos have been effective in comparing and measuring ways that experienced and novice teachers attend to particular moments in recorded classrooms (Dessus, Cosnefroy, & Luengo, 2016; Cortina, Miller, McKenzie, & Epstein, 2015; van den Bogert, Bruggen, Kostons, & Jochems, 2014). For example, Dessus et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dessus et al . (2016) used eye‐tracking technology in comparing less and more experienced teachers’ viewing of a classroom video. They found that less experienced teachers attempted to focus on multiple students, whereas more experienced teachers were able to perceive all students but focus on select sets of students.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the study by Dessus et al (2016) , ratios were computed for analyses rather than using raw values to compare variances in the observed values because there was no time limitation to complete the reading activity. Thus, for eye-tracking data analyses, each page of the document was divided in two areas of interest (AOIs), the text and picture areas (see Figure 2 for an example), and ratio values were computed for the number of fixations, duration of fixations, and gaze length on pictures (i.e., uninterrupted sequences of fixations within an AOI), relative to the summed data for both AOIs.…”
Section: Methodsmentioning
confidence: 99%
“…An effective approach towards students' visual attention tracking using an eye tracking methodology to solve multiple choice type problems is addressed in [238]. An information encapsulating process of teacher's consciousness towards the student's requirement using visual tracking is presented in [239], which is beneficial for classroom management system. To facilitate computer educational research using eye tracking methods, a gaze estimation methodology is proposed, which keeps record of a person's visual behavior, reported in [240].…”
Section: Educationmentioning
confidence: 99%